Breast carcinoma in a dog: sensitivity and specificity between cytopathology and histopathology - Cuellar, Paola Alejandra Montenegro; Rocha, Noeme Sousa; de Souza, Natália Freitas; Dinau, Fernando Carmona (Brazilian Journal of Veterinary Medicine, 2024)
This study evaluated the accuracy of mammary carcinoma diagnoses in female dogs through cytological exams (FNA) compared to histopathological diagnoses. The presence of neoplasia and the effectiveness of procedures at the Pathology Laboratory of the Veterinary Hospital of the FMVZ of Unesp Botucatu, were analyzed. Between 2015 and 2020, a total of 1100 mammary neoplasms were identified, of which 569 were mammary carcinomas. Fifty cytological samples were selected and analyzed to determine occurrence, age at presentation, and the most affected breeds, as well as to verify the obtained diagnoses. Mammary carcinoma constituted for 51.72% of the registered cases. A higher occurrence was observed in mixedbreed female dogs, at 40.42%, followed by Poodles at 17%. The most common age at diagnosis was 10 years, and in 65.55% of cases, the dogs had not been previously spayed. 9.31% of the animals had received contraceptives, while 14% had given birth and 14.58% had presented symptoms of pseudopregnancy at some point in their lives. In the test results, a 70% agreement between cytology and histology was observed, with a 30% disagreement between them. Statistically, a sensitivity of 79.32% and a specificity of 57.14% were reflected. Intact and older female dogs represent a significant risk of developing mammary carcinoma. Although the protocol for processing and interpreting cytological samples is well established, the results do not reach the level of excellence observed in previous studies.